Internationalization process of higher education in Brazil and academic mobility: implications for university management in Brazil - Franklin, Luiza Amália; Zuin, Débora Carneiro; Emmendoerfer, Magnus (Universidade Estadual de Campinas, 2018)
Universities deal with the international context since their genesis, when they were called "International Communities", due to the aim for universalization of expertise and knowledge. Nowadays, the institutional opening took a strategic role for these organizations, becoming part of the development  plans. Considering the importance that globalization has brought to all types of relations among countries and the investment that the Brazilian government has made in fostering international opening of higher education, it wasnoticed the importance of studying this process in the Brazilian context. This research sought, then, to comprehend the internationalization process, as well as to discuss its implications to the Brazilian university management, emphasizing the academic mobility. Therefore, it was developed an analytical research that brought a theoretical mapping on the internationalization of higher education and academic mobility in the university management context in Brazil, as well as its concepts and effects in the recent years, besides the forecast to the higher education. It was possible to verify financial, technological, cultural and social implications of this process not only to the university management, but also to society in general. Concluding, it was possible to indicate that the internationalization of the Brazilian higher education is a paradox; it brings out benefits to the development of academics and results to the country (besides following the worldwide trend), at the same time that it is seen as a weakening agent of the national sovereignty and an economic tool that favors only a few people due to its passive way of action, focused on out-mobility as it sends out scholars from whom is expected economic feedback.